Progesterone peak influences embryonic developmental morphokinetics on trigger day? A retrospective study - D. Baldini; V. M. Bartoli; A. Mastrorocco; D. Ferri; M. Dellino; A. S. Laganà; S. Hatirnaz; G. M. Baldini; A. Malvasi; A. Vimercati; G. Trojano (Journal of Ovarian Research)
Abstract Objective Premature Progesterone Rise (PPR) is characterized by elevated serum progesterone concentrations either towards the end of the follicular phase or on the trigger day, surpassing a pre-defined threshold value. Aim of the study is to evaluate the impact of PPR exceeding 1.5 ng/ml at the time of hCG-trigger on embryo morphokinetic parameters and to identify predictive biomarkers of in IntraCytoplasmic Sperm Injection (ICSI) cycles outcomes. Methods It is a retrospective study including patients underwent ICSI cycles in the period 2020–2023. 58 patients were recruited in the study group showing P levels in the trigger day greater than or equal to 1.5 ng/ml. A matching control group of 58 patients with P levels below 1.5 ng/ml was after selected. The general characteristics of these patients, including age, Body Mass Index (BMI), antral follicle count (AFC), anti-Müllerian hormone (AMH) and follicle-stimulating hormone (FSH) levels, the type of infertility and smoking/non-smoking patients, were recorded on the day of their initial visit. Subsequently, data were collected regarding the number of eggs retrieved, mature eggs, successfully fertilized eggs, and embryos reaching the blastocyst stage. Additionally, the timing of embryonic development and the quality of obtained blastocysts, as assessed by the degree of expansion and the characteristics of the inner cell mass (ICM) and trophectoderm (TE), were evaluated using Time-Lapse technology. Results Elevated P levels exceeding 1.5 ng/ml on the trigger day were directly associated with a significantly larger number of antral follicles, consequently leading to a higher count of retrieved eggs, mature eggs, successfully fertilized eggs and embryos reaching the blastocyst stage. Furthermore, the analysis of morphokinetic parameters indicated faster division times and a notably greater number of high-grade blastocysts in the study group compared to the control group. Conclusions P levels ≥ 1.5 ng/ml on the trigger day did not negatively impact embryonic morphokinetic parameters, instead resulting in faster embryo development in the initial stages.